2022
DOI: 10.1186/s12302-022-00635-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibiotic resistance genes in drinking water sources of the Douhe Reservoir, Tangshan, northern China: the correlation with bacterial communities and environmental factors

Abstract: Background Antibiotics and antibiotic resistance genes (ARGs) threaten ecological sustainability and human health, especially the drinking water sources of the Douhe Reservoir, which have critical significance amid their direct use by people and the ecological hub of flora and fauna. Although antibiotics and ARGs pollution in reservoirs have been reported, it is of no practical significance to only study the changes (increase or decrease) of the abundance and diversity of ARGs, and it is more i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 72 publications
1
2
0
2
Order By: Relevance
“…The kind of significant correlation (p-value <0.05) observed in the current study between bacterial communities and antibiotic residues led to the speculation that various responses of bacterial communities to antibiotic residues in the environment select for antibiotic resistance in opportunistic bacteria [ 70 ]. Consistent with other studies, the correlation between bacterial communities and ARGs observed in the current study indicates that bacteria are the major sources and spreaders of ARGs [ 70 , 71 ]. The physicochemical parameters in NW-E and NW-C DWPF create favourable conditions for the survival of bacteria and may directly or indirectly influence the variation and levels of ARGs [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The kind of significant correlation (p-value <0.05) observed in the current study between bacterial communities and antibiotic residues led to the speculation that various responses of bacterial communities to antibiotic residues in the environment select for antibiotic resistance in opportunistic bacteria [ 70 ]. Consistent with other studies, the correlation between bacterial communities and ARGs observed in the current study indicates that bacteria are the major sources and spreaders of ARGs [ 70 , 71 ]. The physicochemical parameters in NW-E and NW-C DWPF create favourable conditions for the survival of bacteria and may directly or indirectly influence the variation and levels of ARGs [ 72 ].…”
Section: Discussionsupporting
confidence: 92%
“…Antibiotic residues, physicochemical parameters and ARGs might prompt the selection of the appropriate bacterial community and subsequently change the microbial composition and diversity [ 70 , 71 ]. No significant differences (p-value >0.05) were observed between bacterial communities and environmental factors using RDA analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of bacterial communities appears to be the primary driver of changes in ARGs. In addition, one study also mentioned that environmental factors, particularly temperature, nitrates, total dissolved nitrogen, and total phosphorus, showed significant correlations with variations in bacterial communities, ARGs, and MGEs [ 39 ].…”
Section: Antibiotic Resistance (Abr) In Aquatic Environmentsmentioning
confidence: 99%
“…Por su parte, el entonces primer ministro del Reino Unido, David Cameron, designó al economista Jim O´Neill para investigar las consecuencias económicas de la RAM ( 12 ). En su informe, expresó la preocupación por las consecuencias de la RAM; entre ellas, la estimación de una tasa de mortalidad creciente para el año 2050 y las consecuencias en la agricultura, la ganadería y la economía en general, que ocasionarían un colapso mundial.…”
Section: Materiales Y Métodosunclassified
“…Por otro lado, se ha observado que la farmacorresistencia microbiana o también llamada resistencia a los antimicrobianos (RAM) ( 9 ) es un problema de salud pública que se presenta cuando los microorganismos (bacterias, hongos, parásitos o incluso los virus) evaden el efecto de los antimicrobianos a través de diferentes mecanismos. Sin embargo, la resistencia que presentan las bacterias ( 10 , 11 ) es de mayor relevancia debido a la magnitud del riesgo y a la velocidad en su desarrollo, ocasionada sobre todo por el uso y el consumo indiscriminado de antibióticos, aunado al manejo inadecuado de sus desechos ( 12 , 13 ). Como consecuencia, se ven comprometidos algunos de los Objetivos del Desarrollo Sostenible (ODS) ( 14 ) como salud y bienestar (ODS 3), fin a la pobreza (ODS 1), hambre cero (ODS 2), agua limpia y saneamiento (ODS 6), trabajo decente y crecimiento (ODS 8) y consumo y producción sostenible (ODS 12), así como alianzas para lograr los objetivos (ODS 17).…”
unclassified